Mismatch repair deficiency is a rare but putative therapeutically relevant finding in non-liver fluke associated cholangiocarcinoma - Goeppert, Benjamin; Rössler, Stephanie; Renner, Marcus; Singer, Stephan; Mehrabi, Arianeb; Vogel, Monika Nadja; Pathil-Warth, Anita; Busch, Elena; Köhler, Bruno Christian; Springfeld, Christoph; Pfeiffenberger, Jan; Rupp, Christian; et al. (British journal of cancer, 2019)
A major molecular pathway of genetic instability in cancer is DNA mismatch repair deficiency. High-level microsatellite instability (MSI-H) is currently the best predictor of responsiveness towards immune checkpoint blockade. Data about the prevalence of high-level microsatellite instability in cholangiocarcinoma (CCA) has been conflicting. We employed a cohort comprising 308 Western-world, non-liver fluke-associated CCAs (159 intrahepatic, 106 perihilar, and 43 distal). We analysed the mononucleotide microsatellite instability marker panel consisting of BAT25, BAT26, and CAT25 and detected MSI-H in 4/308 CCAs (1.3%). Patients affected by MSI-H CCA had mostly an atypical histomorphology (p = 0.004), showed a longer overall survival, although having a high tumour stage, and were of younger age. Correlation analysis of microsatellite instability status with tumour-infiltrating immune cells, MHC I, and PD-L1 expression in the same cholangiocarcinoma cohort showed higher numbers of CD8 + T cells, FOXP3 + regulatory T cells, CD20 + B cells and high or at least moderate MHC I expression levels in MSI-H CCAs. Even though the overall number of MSI-H CCAs is low, the dismal prognosis of the disease and the therapeutic option of immune checkpoint blockade in the respective patients justify MSI testing of cholangiocarcinoma, particularly in younger patients showing an atypical histomorphology.
Published: 31 October 2018
Gesehen am 08.05.2019